2020
DOI: 10.1002/pa.2326
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and income inequality: Do technological changes and worker's position matter?

Abstract: The technological progress in artificial intelligence (AI) has led to mass unemployment and various types of inequalities in the recent years. This study is an attempt to see how income inequality has increased with the changes in technology. The study also investigated how technology such as AI has affected (directly or indirectly) to working position and working process of workers. Analysis of the study is based on the data of automation and Gini‐coefficients. The study finds that the relationship between AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Goyal & Aneja (2020) demonstrated that the Gini coefficient of developing countries is higher than that of developed countries, which indicates that the degree of income inequality in developing countries is higher than that in developed countries [6]. The critical reason is that developing countries still have a significant gap in artificial intelligence technology and automation, and their production methods are still relatively primitive.…”
Section: Ai Affects the Gap Between Rich And Poor In Different Countriesmentioning
confidence: 99%
“…Goyal & Aneja (2020) demonstrated that the Gini coefficient of developing countries is higher than that of developed countries, which indicates that the degree of income inequality in developing countries is higher than that in developed countries [6]. The critical reason is that developing countries still have a significant gap in artificial intelligence technology and automation, and their production methods are still relatively primitive.…”
Section: Ai Affects the Gap Between Rich And Poor In Different Countriesmentioning
confidence: 99%
“…AI systems are already contributing to SDG 11 in numerous cities around the world, but their use for smart cities has been criticized for lacking genuine sustainability and citizen-centric approach as well as for being focused on highly developed economies [187]. Moreover, several targets ( ) and potential bias [192,[200][201][202][203][204][205]. Indeed, AI has been widely criticized for augmenting inequality, bias, discrimination, and reproducing hierarchies [204].…”
Section: Group 3: Ai As a DImentioning
confidence: 99%
“…In addition to closely monitoring AI development and trends to ensure fairness in the workplace, government leaders need to prepare for the possibility of unprecedented mass unemployment in the near future caused by relentless advances in AI in many industries. The increased use of AI has already led to significant job losses and to increased levels of income inequality in many countries (Goyal & Aneja, 2020). For example, driverless vehicles guided by AI are replacing human taxi drivers, bus drivers, and truck drivers, and many banks have drastically reduced employee numbers through the increased use of AI and automated online banking services.…”
Section: Preparing Global Society For Co-existence and Effective Coll...mentioning
confidence: 99%